Perilaku Harga Pembukaan (Opening Price): Noise dan/atau Overreaction (Studi Empiris Berbasis Intraday Data, 2006) - Sumiyana Sumiyana; HENDRIK GAMALIEL (The Indonesian Journal of Accounting Research, 2013)
This study examines whether opening price behavior is respon-sible for the noise and overreaction in the Indonesian Stock Exchange using intraday data in every 30 minutes interval. This study extends Sumiyana (2007b) who finds that noise has occurred during trading and nontrading period, overnight and lunch break nontrading session, and the first and second trading sessionoccurred. However , he is not clear which prices contains noise and overreaction. I select my sample based on trading frequency from January to December 2006 of LQ45's stocks that are actively traded in Jakarta Stock Exchange (now Indo-nesian Stock Exchange). The study finds that noise and overreaction phenomena always occur in the opening price. In addition, the study also shows that investors actually correct the noise and overreaction that come to pass at the first 30 minutes interval in every trading ses-sion.